Analysis Of Business Licensing Facilitation Policy For Msmes - Rais Muhamad Falah; R. Ira Irawati; Nina Karlina (Green Publisher Indonesia, 2024)
In line with the progression of time, business licensing has also become a focus of the Central Government, especially with the opening of extensive investment opportunities through the enactment of Law Number 11 of 2020 concerning Job Creation, or the Omnibus Law. The Job Creation Law has led to adjustments in several laws, one of which is in the realm of licensing in Indonesia. One of the changes in licensing is the establishment of Government Regulation Number 5 of 2021 concerning the Implementation of Risk-Based Business Licensing, referred to as the Business Licensing Regulation. This study aims to analyze how the implementation of risk-based business licensing policies is carried out by examining Regional Regulation No. 10 of 2021 of the City of Bandung on the Implementation of Business Licensing. The results indicate that the implementation of the OSS RBA-based business licensing policy for MSMEs in Bandung City is maximized in accordance with the theories of Edward and Van Metter Van Horn. The implementation results also align with Regional Regulation No. 10 of 2021 of Bandung City. Each indicator shows results with each implementation of Regional Regulation No. 10 of 2021 carried out by the DPMPTSP of Bandung City. The implementation is in accordance with Regional Regulation No. 10 of 2021 of Bandung City and also aligns with the theories of Edward and Van Metter Van Horn.